2017
DOI: 10.1093/ons/opx175
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Accuracy of the Subthalamic Nucleus in Deep Brain Stimulation Surgery: Comparison Between 3 T T2-Weighted Magnetic Resonance Imaging and Microelectrode Recording Results

Abstract: STN MRI-based targeting is accurate in the majority of cases on the first and second side of surgery. In 43% of implanted electrodes, we found a relevant deviation of more than 1 mm, supporting the concept of MER as an important tool to guide and optimize targeting and electrode placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…From each patient's data set, we concluded that the DBS lead artefact on postoperative CT reflected the actual lead position within the STN reliably as we found no difference between the reconstructed image-based trajectories through the STN and their corresponding electrophysiological activity. This is in line with previous work by our and other groups ( Hamani et al, 2005 ; Kocabicak et al, 2013 ; Nowacki et al, 2017 ; Schlaier et al, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…From each patient's data set, we concluded that the DBS lead artefact on postoperative CT reflected the actual lead position within the STN reliably as we found no difference between the reconstructed image-based trajectories through the STN and their corresponding electrophysiological activity. This is in line with previous work by our and other groups ( Hamani et al, 2005 ; Kocabicak et al, 2013 ; Nowacki et al, 2017 ; Schlaier et al, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…For detailed description of our targeting approach and operative procedure we refer to previously published reports of our group ( Nowacki et al, 2017 ). In summary, each patient underwent preoperative MRI to target the STN.…”
Section: Methodsmentioning
confidence: 99%
“…One study showed that the final stimulation site, based on MER and intraoperative stimulation, was located more lateral and superior than both atlas and MRI based targets . Also, newer studies show discrepancies comparing borders on T2 and SWI MRI sequences compared to the electrophysiological STN . Further research is needed to evaluate the impact of these newer techniques on target accuracy and clinical outcome …”
Section: Discussionmentioning
confidence: 99%
“…12,31 MER may have its advantages in identifying the electrophysiologic footprint of some target structures 11 that can differ from the MRI-derived target boundaries and can be performed under general anesthesia or dopaminergic medication. 24,32,33 The widespread rates of MER-based adjustments in the literature may be explained by the variable a priori use of single or multiple microelectrodes. 11 Often, more than one, for example, two to three microelectrodes are used in a classical neurophysiologic mapping approach.…”
Section: Intraoperative Neurophysiologic Recordingmentioning
confidence: 99%